Public perceptions of female police officers on patrol - Leger, Kristen (American journal of criminal justice, 1997)
Women in policing have been the subject of considerable study for the past 20 years. While women perform as well as men in various patrol assignments and situations, they still face a significant amount of disapproval from the male police personnel population. Citizens, however, have shown a greater acceptance of women in this male-dominated occupation and a greater confidence in women’s abilities to effectively perform difficult patrol tasks. The purpose of the present research is to determine the perceptions that residents of two Kentucky counties have of female patrol officers and if those perceptions affirm previous findings. The socioeconomic foundations for those residents’ perceptions are also examined. The research instrument consisted of 17 closed-ended and matrix questions. Two hundred responses were obtained. The results of this study will indicate the public’s growing acceptance of women in this non-traditional gender role, which is a requisite development for the overall objective of attaining equality and equity for women in police work. Recommendations are presented for the purposes of explaining the inevitable changes in the gender makeup and purposes of police work and the need for police personnel and the public to accept those changes.